Educational robotics program to improve meaningful learning in fourth grade students in the area of Science and Environment of the educational institution San Roque - Castrovirreyna, 2015 - Isabel Margarita, Isabel Margarita (2018)
The present article is the review of an investigation that had as objective to develop an Educational Robotics Program to improve the significant learning of the Area of ​​Science and Environment in fourth grade students of the educational institution San Roque -Castrovirreyna, 2015. The design It was quasi-experimental in a sample of 68 students. The applied instrument for the measurement of learning in the area of ​​Science and Environment was constructed based on the Likert attitude scale of five points, validated by the criteria of judges and a reliability of 87%. The results show that the educational robotics program has a positive and significant influence on learning in the area of ​​Science and Environment; the intensity of the influence is 55.9%, which is very significant.